The crisis-woman : body politics and the modern woman in fascist Italy - Chang, Natasha V., 1971- (Toronto Italian studies., 2014)
Using a rich assortment of scientific, medical, and popular literature, Natasha V. Chang's The Crisis-Woman examines the donna-crisi 's position within the gendered body politics of fascist Italy.